Testing of nutmeg shell as a lightweight concrete material in terms of volume weight and compressive strength value - Budiman Budiman (Center of Techonolgy (COT), Engineering Faculty, Hasanuddin University, 2020)
Lightweight concrete can be defined as a type of concrete which includes an expanding agent in that it increases the volume of the mixture while giving additional qualities such as nailibility and lessened the dead weight. The nutmeg shell has the characteristics of light and hard skin testure so that it has the potential to be used as a material for lightweight concrete. The purpose of this study is to determine the aggregate characteristic value and the compressive strength value of concrete using the DOE (department of environment) method and referring to standards SNI. Variation of use nugmet shell toward the weight volume of concrete is 10%, 20%, 30%, 40% and 50%. This research is a sample-based laboratory research and analysis of aggregate characteristics and concrete compression test. The research result shows that the use of nutmeg skin as a coarse aggregate material in the concrete mixture affects the volume weight of the concrete. The weight of the concrete gets lighter along with the higher the percentage used. The average volume weight obtained was 1810.06 kg / m3. Based on the weight of the concrete sample, it is classified as light structure, includes concrete with low density and includes lightweight aggregate concrete. The compressive strength values for the characteristics of concrete at a composition of 10%, 20% and 30% were obtained at 28.42 kg/cm2, 31.65 kg/cm2 and 32.68 kg/cm2 which increased while the use of nutmeg shells at 40% and 50% compositions was obtained. values of 29.09 kg/cm2 and 27.38 kg/cm2 decreased at the age of 28 days. The increase in the value of the compressive strength of concrete (fck') occurred starting at the composition of 20% and 30% at 10.20% and 13.03% and begin to decrease at the composition of 50% by 3.65%. Lightweight concrete from nutmeg shells has an weight of 1810,06 kg/m3 and a maximum compressive strength value of 3,2 MPa so that the concrete is in the category lightweight structure.